The immunomodulatory effects of vitamins in cancer - Munteanu, Camelia; Mârza, Sorin Marian; Papuc, Ionel (Frontiers in Immunology, 2024)
Nutrition may affect animal health due to the strong link between them. Also, diets improve the healing process in various disease states. Cancer is a disease, where the harmful consequences of tumors severely impair the body. The information regarding the evolution of this disease is extrapolated from human to animal because there are few specific studies regarding nutritional needs in animals with cancer. Thus, this paper aims to review the literature regarding the immunomodulatory effects of vitamins in mammal cancer. An adequate understanding of the metabolism and requirements of nutrients for mammals is essential to ensuring their optimal growth, development, and health, regardless of their food sources. According to these: 1) Some species are highly dependent on vitamin D from food, so special attention must be paid to this aspect. Calcitriol/VDR signaling can activate pro-apoptotic proteins and suppress anti-apoptotic ones. 2) Nitric oxide (NO) production is modulated by vitamin E through inhibiting transcription nuclear factor kappa B (NF-κB) activation. 3) Thiamine supplementation could be responsible for the stimulation of tumor cell proliferation, survival, and resistance to chemotherapy. 4) Also, it was found that the treatment with NO-Cbl in dogs is a viable anti-cancer therapy that capitalizes on the tumor-specific properties of the vitamin B12 receptor. Therefore, diets should contain the appropriate class of compounds in adequate proportions. Also, the limitations of this paper are that some vitamins are intensively studied and at the same time regarding others, there is a lack of information, especially in animals. Therefore, some subsections are longer and more heavily debated than others.